2016
DOI: 10.3109/02713683.2016.1141965
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool for the Assessment Oxidative Stress in Age-Related Macular Degeneration: Thiol/Disulfide Homeostasis Revisited

Abstract: A greater extent of thiol consumption occurred in AMD patients compared to age-matched healthy controls. However, despite the similar levels of total thiol levels between several grades of AMD, the plasma native TDR value was decreased in accordance with the severity of the disease, which reflected the disease grade better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Native thiol and TT levels were found to be lower in central serous chorioretinopathy and macular degeneration patients compared to control subject [79][80][81].…”
Section: Ophthalmic Disordersmentioning
confidence: 75%
“…Native thiol and TT levels were found to be lower in central serous chorioretinopathy and macular degeneration patients compared to control subject [79][80][81].…”
Section: Ophthalmic Disordersmentioning
confidence: 75%
“…Patients with AMD had significantly lower plasma levels of thiol and native thiol/disulfide ratios (TDRs) compared to those of healthy controls. The plasma native TDR decreased in accordance with the increasing severity of AMD [169].…”
Section: Serummentioning
confidence: 80%
“…The role of oxidative stress in pathogenesis of various ocular disease including the cataracts, age related macular degeneration, central serous chorioretinopathy, pterygium, dry eye and the keratoconus were reported before. 3,[12][13][14][15][16][17][18] Altınisik and et al showed increased oxidative stress index (OSI) and lower total antioxidant status (TAS) in the humor aqueous samples of the retinal vein occlusion patients and they blamed hypoxia, ischemia and reperfusion damage by the reactive oxygen radicals. 3 Becatti et al found higher reactive oxygen species production and membrane lipid peroxidation in the erythrocytes of the retinal vein occlusion patients due to the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%